Integration of Tauhid (Faith) Element in Biology Education - Sayyidah Nusaibah Mohd Salehudin; Zanaton H Iksan (Universitas Riau, 2017)
Tauhidik science is one of the Islamization of Knowledge efforts in the field of education. This effort was initiated by many Islamic scholars to fight against secularism. To implement the elements of faith (Tawhid) in Science Education, Al-Qur'an is the ultimate guide. The aim of this concept paper is to describe the elements of faith in biology education. In this concept paper, the definition of Tauhidik Science is specified. Next, the strategy of integration of Tauhidic element in Biology is explained. The concept paper also proposes that the implementation of elements of faith made in more in-depth for each subtopic studied. The implementation of Faith element in Science Education is expected to produce a generation whose life is guided by the Quran and have Ulul Albab thought which means having a deep rooted knowledge and strong belief to Allah s.w.t, thus forming the next generation that brings prosperity to the mankind.